INFLUENCE OF INDIVIDUAL CHARACTERISTICS, INFORMATION TECHNOLOGY, AND SERVICE ON TAXPAYER COMPLIANCE WITH SOCIALIZATION AS A MEDIATION (Case Study of General Public in Surabaya City) - Rachmadani, Adelia Putri; Aini, Farah Nurul; Romadhoni, Alfian (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
This study aimed to determine the influence of internal factors (characteristics with indicators of awareness and moral obligation) and external factors (technology and services) on taxpayer compliance. This research was conducted in the city of Surabaya. Sampling was carried out using the Convenience Sampling Method (sample selection based on convenience) using 100 respondents from the questionnaire. The data collection method used in this research is the survey method using a questionnaire. The results of the research show that individual characteristics have a positive effect on socialization. Information technology has a positive effect on socialization. Service has a positive effect on socialization. Individual characteristics have a positive effect on taxpayer compliance. Information technology has a positive effect on taxpayer compliance. Service has a positive effect on taxpayer compliance. Socialization has a positive effect on taxpayer compliance. Individual characteristics positively affect taxpayer compliance through socialization as a mediator. Information Technology Has a Positive Effect on Taxpayer Compliance through Socialization as a Mediator. Service has a positive effect on taxpayer compliance through socialization as a mediator.